2013
DOI: 10.1038/srep02683
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Enhances Chondrogenesis and Prevents Terminal Differentiation through PI3K/Akt/FoxO Dependent Anti-Apoptotic Effect

Abstract: Hypoxia, a common environmental condition, influences cell signals and functions. Here, we compared the effects of hypoxia (1% oxygen) and normoxia (air) on chondrogenic differentiation of human mesenchymal stem cells (MSCs). For in vitro chondrogenic differentiation, MSCs were concentrated to form pellets and subjected to conditions appropriate for chondrogenic differentiation under normoxia and hypoxia, followed by the analysis for the expression of genes and proteins of chondrogenesis and endochondral ossif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
96
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(102 citation statements)
references
References 46 publications
4
96
1
1
Order By: Relevance
“…However, the determination of cell fate is typically a multistage decision involving multiple signaling pathways in a spatiotemporal manner. In addition to single candidates, it is likely that multiple signaling pathways are able to act in concert or even synergistically (21). The involvement of multiple signaling pathways upon exposure to distinct oxygen tension is also suggested by observations in our current study.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…However, the determination of cell fate is typically a multistage decision involving multiple signaling pathways in a spatiotemporal manner. In addition to single candidates, it is likely that multiple signaling pathways are able to act in concert or even synergistically (21). The involvement of multiple signaling pathways upon exposure to distinct oxygen tension is also suggested by observations in our current study.…”
Section: Discussionsupporting
confidence: 64%
“…Moreover, this pathway is associated with both chondrogenesis and the induction of hypertrophic differentiation in articular cartilage during the pathological development of osteoarthritis (20). Alternatively, it has recently been reported that the activity of the PI3K/AKT/FOXO pathway is influenced by oxygen tension and is able to enhance chondrogenesis, inhibit hypertrophic differentiation, and prevent endochondral ossification (21). Also, SMAD signaling induced by members of the TGF-β/BMP family of growth factors is influenced by oxygen tension (22).…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia was shown to enhance chondrogenic differentiation of MSCs [424] and chondrocytes [425]. Following these findings, it is reasonable to hypothesize that the application of mechanical loading under hypoxic conditions further enhances chondrogenic differentiation and maturation of tissue engineered cartilage constructs.…”
Section: Future Directionsmentioning
confidence: 89%
“…Hypoxia was suggested to promote chondrogenesis in rat MSCs [194] and human MSCs [195]. Thus we investigated the effect of hypoxia on hMSC chondrogensis in our system with pathway inhibitors.…”
Section: Hypoxiamentioning
confidence: 99%
“…MSCs [195]. Treatment with basic fibroblast growth factor (FGF-2) during MSC expansion could inhibit the differentiation of MSCs [196,197].…”
Section: Culture Conditions Of Mscs During Expansion and Differentiationmentioning
confidence: 99%